Implementasi Gaya Mengajar Berbasis Kecerdasan Naturalis dan Kinestetik pada Kelas 1 di MIM PK Kartasura - Widyawulandari, Rizki; , Drs. Mulyadi,M.Pd (2017)
This research aims to: 1) Determine whether the teacher has mastered the style taught naturalist and kinestethic 2) Describe implementation of teaching style based on natural intelligence, and 3) Describe implementation of teaching style based on kinestetic intelligence on the first grade of MIM PK Kartasura. This is a qualitative research with case study design. The informants of this research are the headmaster, guardian angel, the teacher of 1A, 1B, and 1C class. The technique of data collection used are observation, deep interview, and documentation. The data analyzed by the steps of collecting, reductioning, serving/presenting, and verifying data. The validity of the data investigation technique is done by the triangulation technique and triangulation source. The results are,1) Teacher has quite to mastered by applying the teaching style based naturalist and kinesthetic. 2) The implementation of teaching style based on natural intelligence began with the preparation which are including Multiple Intelligence Research test, teachers training, and making lesson plan. In teaching activity using teaching style, strategy, media, methods, variation of teaching and special characteristic of natural teaching. The difference between it and common teaching style is using nature applied in learning activity and the obstacles of difficulties in disciplining students and lack of teacher's understanding and creativity. The solution is giving rules and consequences, training and evaluating the teachers in form of report. 3) The implementation of teaching style based on kinestetic intelligence began with the preparation which are including Multiple Intelligence Research test, teachers training, and making lesson plan. In teaching activity using teaching style, strategy, media, methods, variation of teaching and special characteristic which is appropriate with kinestetic intelligence. In kinestetic teaching, the teacher is more energetic using stutdent's motor neuron function which is considered as a place to tell something. The obstacle is difficulty in managing energetic students but the teacher is not creative. The solution is using the energetic student's as the learning media, making learning contract, and training and evaluating the teachers in form of report. Keywords: Natural intelligence, kinestetic intelligence, teaching style.